Multi-target regulatory effects of rhaponticin in a rat model of hepatic fibrosis revealed by non-targeted metabolomics - Yang, Min; Jiang, Dihua; Huang, Longfei; Zhang, Tao; Guo, Wenfen; Lin, Wenyan; Zhao, Jiali; Wei, Yunsheng; Peng, Lang; Hao, Yong-Jia; Zhou, Ying (Frontiers in Pharmacology, 2025)
IntroductionHepatic fibrosis (HF), a progressive chronic liver disease, is a serious threat to global public health. The lack of preventive and therapeutic strategies has created an urgent need for effective anti-fibrosis agents. There is growing evidence that natural products might provide safe and effective interventions for HF. Among them, rhaponticin (RHA), a stilbenoid glucoside natural product isolated from medicinal plants of Rheum L. of Polygonaceae Juss. has many pharmacological activities such as anti-inflammatory, antioxidant, antiproliferative, and antithrombotic properties. However, its effects on HF remain unclear.MethodsHerein, we investigated the effects of RHA against HF on the carbon tetrachloride (CCl4)-induced hepatic fibrosis and the underlying mechanism in rats. Functional, histopathological, and protein-level indicators of liver insult were evaluated. Moreover, serum metabolites were assessed by non-targeted metabolomics.Results and discussionThe results showed that RHA improved liver functions and histopathological features in the liver of CCl4-treated rats, and alleviated the expression of α-SMA and type I collagen. Meanwhile, RHA also modulated endogenous metabolite levels in rats with HF, targeting glycerophospholipid metabolism signaling and other pathways. These findings confirmed the protective effects of RHA against hepatic fibrosis in rats by exerting multi-target effects via multiple signaling and metabolic pathways. Which may be of use in developing more effective RHA-based therapeutic strategies for hepatic fibrosis.